DEVELOPMENT OF PERSPECTIVE ORGANO-HYBRID COMPOSITION BASED ON MODIFIED POLYACRYLONITRILE DURING REPAIR AND INSULATION OPERATIONS IN WELLS - A. S. Gumerova; R. N. Yakubov; L. E. Lenchenkova; D. A. Ilash (Наука. Инновации. Технологии, 2022)
Introduction: Due to the entry of most of the fields into the final stage of development, the relevance of issues related to improving the efficiency of repair and insulation operations (RIO) conducted at the complicated well stock increases. In justifying RIO technologies, primarily focuses on the selection of chemical reagents for the insulating screens formation in the reservoir flooded zones. Materials and methods: A new organo-hybrid composition based on polyacrylonitrile was obtained by hydrolysis with sodium silicate. A complex of rheological studies was carried out to determine the structural and mechanical properties of the composition with hydrochloric acid. Spectral studies were performed to clarify the mechanism of gel formation of a new organo-hybrid composition. Results and discussion: Analysis of the new composition based on hydrolyzed polyacrylonitrile experimental studies results revealed a synergistic effect associated with the presence of both viscous-plastic and viscous-elastic properties, ensuring high efficiency of its application in reservoir conditions. The mechanism of gelation of the new composition based on the COM-C reagent apparently occurs due to the formation of polymer ilaments reinforcing the silicate component and siloxane bonds formation is achieved by means of dimers, which are "bridges" between globules. Conclusion: Hydrolyzed by sodium silicate polyacrylonitrile is a promising reagent for the gel-forming composition, capable to form a durable insulating screen in highly permeable watered zones of the formation when reacting with hydrochloric acid.